Effectiveness of Using Power Point Media in Indonesian Language Learning in Elementary Schools - Kamasiah; Nurmina Labalawa; Rika Septi Riana; Rusman Masiri (Jurnal Wawasan Sarjana, 2025)
PowerPoint is not only a teacher's tool, but also a learning tool that supports the development of 21st century skills in students. The effectiveness of using PowerPoint media in learning Indonesian in Elementary Schools has proven to be quite significant in improving the quality of the teaching and learning process. The purpose of this study was to determine the Effectiveness of Using PowerPoint Media in Learning Indonesian in Elementary Schools. Qualitative research methods that aim to describe the use of PowerPoint media in learning Indonesian by fourth grade teachers at SD Negeri 1 Batulo. Qualitative research was chosen because it allows researchers to explore in depth the learning process, material delivery strategies, and interactions that occur between teachers and students during learning. The results of the study showed that the use of PowerPoint media in learning Indonesian in fourth grade at SD Negeri 1 Batulo has proven to be effective in improving students' understanding and interest in learning. Attractive and interactive visual displays help students focus more and understand the material better. In addition, PowerPoint allows teachers to deliver material more systematically and efficiently, creating a more enjoyable learning atmosphere. Thus, the use of PowerPoint as a learning medium is an effective strategy in improving the quality of learning and student learning outcomes.